If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-3) = f + 10 Multiply 5 * -3 -15 = f + 10 Reorder the terms: -15 = 10 + f Solving -15 = 10 + f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-1f' to each side of the equation. -15 + -1f = 10 + f + -1f Combine like terms: f + -1f = 0 -15 + -1f = 10 + 0 -15 + -1f = 10 Add '15' to each side of the equation. -15 + 15 + -1f = 10 + 15 Combine like terms: -15 + 15 = 0 0 + -1f = 10 + 15 -1f = 10 + 15 Combine like terms: 10 + 15 = 25 -1f = 25 Divide each side by '-1'. f = -25 Simplifying f = -25
| 54-2x-x^2=0 | | 2x+4(-22)+4+3(3)=3 | | x^2-2x^5+8x+7x^7+9= | | 7+(2x+1)=9x+27 | | x-12=8x+16 | | Ln(2x^2-1)=0 | | -3(n-8)=-3+6n | | 2y+12(4)+4(3)=16 | | 4.39N+3.44N=66.44 | | 5y^2-10x=4 | | =12L | | 3e^4x=26 | | 2n^0*3n= | | x(5-x)=-6 | | (3-7)= | | x-30=46 | | x^2+5x-2=3x+6 | | 4s^2+4s^2= | | f(z)=4x-1 | | 5*x^2=2x | | 5x*2=2x | | 10x-17=9x+5 | | 335-x=15 | | 4s^2+4s^2+6s-1+8-5s= | | 2+12=5+-9 | | 10x^2+40x-2000=0 | | 15a+3=33 | | 2x+12=5-9 | | 7(4p+2q+3r)= | | 29=5-3x | | 7x-(7+4x)= | | -8(u+5)=-64 |